2020
DOI: 10.1111/jgs.16909
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hospitalization with Long‐Term Cognitive Trajectories in Older Adults

Abstract: IMPORTANCE Hospitalizations are associated with cognitive decline in older adults. OBJECTIVE To determine the association between hospitalization characteristics and the trajectory of cognitive function in older adults. DESIGN Population‐based longitudinal study of cognitive aging. SETTING Olmsted Medical Center and Mayo Clinic, the only centers in Olmsted County, Minnesota, with hospitalization capacity. PARTICIPANTS Individuals without dementia at baseline, with consecutive cognitive assessments from 2004 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…As opposed to Sprung et al . [ 2 ] our study found that number of hospitalisations was not associated with cognitive decline . We additionally found that although the participants with delirium spent more days in hospital during the 1 year study period, total duration of hospital stay was not associated with cognitive decline in our models.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As opposed to Sprung et al . [ 2 ] our study found that number of hospitalisations was not associated with cognitive decline . We additionally found that although the participants with delirium spent more days in hospital during the 1 year study period, total duration of hospital stay was not associated with cognitive decline in our models.…”
Section: Discussionmentioning
confidence: 60%
“…In a number of large studies, acute hospitalisation has been shown to be adversely associated with increased risks of incident dementia and accelerated trajectories of cognitive decline [ 1–6 ]. The components driving these associations are unclear but factors demonstrated to confer increased risk of worse cognitive outcomes following hospitalisation include non-elective admission [ 1 , 2 ], critical illness [ 3 , 4 ], admissions for medical conditions [ 2 ] and stroke [ 5 ], longer admissions [ 4 ] along with a number of baseline comorbidities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a growing body of evidence indicates that critical illness and medical encounters such as hospitalization in older people increase their risk of long‐term cognitive impairment 189–195 . The emergence of novel coronavirus disease in 2019 (COVID‐19) has resulted in tens of thousands of hospitalizations.…”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…A growing body of evidence indicates that critical illness and medical encounters such as hospitalization in older people increase their risk of long-term cognitive impairment. [200][201][202][203][204][205][206] The emergence of novel coronavirus disease in 2019 (COVID-19) resulted in more than 1.3 million hospitalizations among U.S. adults age 65 and older between January 1, 2020, and July 24, 2021. 207 This has the potential to increase the number of cases of cognitive impairment following critical illness.…”
Section: Other Risk Factorsmentioning
confidence: 99%